2016
DOI: 10.1007/s00240-016-0933-2
|View full text |Cite
|
Sign up to set email alerts
|

Are there any predictors of pyonephrosis in patients with renal calculus disease?

Abstract: The objective of the study is to identify factors predicting development of pyonephrosis in patients of renal calculus disease (RCD), as this knowledge is largely unknown. Patients of RCD without pyonephrosis (Group 1) or with pyonephrosis (Group 2) presenting between December 2013 and November 2015 were evaluated. All patients of RCD who had undergone either percutaneous nephrostomy (PCN) or surgical management (percutaneous nephrolithotomy/pyelolithotomy/nephrectomy) were included. Patients treated conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…Previous studies evaluated factors associated with PYO in patients with urinary stones. Patodia et al 5 , analysed a cohort of 91 patients with PYO and 410 individuals without PYO treated at a single center for urinary stone disease and showed that risk factors for pyonephrosis were delayed presentation, large stone size, severe hydronephrosis and poor renal function. Our results corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies evaluated factors associated with PYO in patients with urinary stones. Patodia et al 5 , analysed a cohort of 91 patients with PYO and 410 individuals without PYO treated at a single center for urinary stone disease and showed that risk factors for pyonephrosis were delayed presentation, large stone size, severe hydronephrosis and poor renal function. Our results corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice the distinction between PYO and uninfected hydronephrosis (HYDRO) is challenging and the molecular mechanisms underlying the shift from HYDRO to PYO in the presence of urinary obstruction are poorly understood 1 , 5 . Previous studies have described various risk factors for PYO in patients with urinary stones such as long-term disease, severe HYDRO, stone size and non-functioning kidney 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patodia retrospectively analyzed 501 patients with kidney stones and found that some factors were closely associated with the occurrence of pyonephrosis, including larger stone volume, severe hydronephrosis, poor renal function, past history of urological surgery, and obstruction caused by other causes than stones [5]. These are considered bene cial in determining which patients with kidney stones are prone to pyonephrosis.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no clear predictive model demonstrating the occurrence of pyonephrosis in patients with kidney stones. Patodia retrospectively analyzed 501 patients with kidney stones and found that some factors were closely associated with the occurrence of pyonephrosis, including larger stone volume, severe hydronephrosis, poor renal function, past history of urological surgery, and obstruction caused by other causes than stones [5]. These are considered bene cial in determining which patients with kidney stones are prone to pyonephrosis.…”
Section: Resultsmentioning
confidence: 99%